United States factors in the Trans Pacific Partnership (TPP) - Tu Linh, Pham Hoang (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Trans Pacific Partnership (TPP) has officially been 12 countries signed on the 5 October 2015 after 5 years of tough negotiations and repeated delays. This is a great success for the redirected strategy of US focus on Asia-Pacific. TPP’s pillars of economic policy “Pivot to Asia” the administration of President Obama. The US use of TPP as the economic engine not only help Washington to maintain its superpowers position in the world, but will also help the Obama administration control rising competition strongly of China in the region. TPP will bring huge benefits for the United States, the participating countries and the Asia-Pacific. Therefore, the participation of US in TPP as the largest partner and important during the negotiations. Received: 9th November 2015; Revised: 17th March 2016; Accepted: 23rd March 2016